A green and effective corrosion inhibitor of functionalized carbon dots. Issue 10 (October 2019) - Ye, Yuwei; Yang, Dongping; Chen, Hao
Abstract: In this work, a green and effective corrosion inhibitor of functionalized carbon dots (FCDs) was synthesized by the conjugation of imidazole and citric acid carbon dots (CA-CDs). The corrosion inhibition behavior of FCDs for Q235 steel in 1 M HCl solution was systematically investigated by electrochemical analysis, corrosion morphology and adsorption isotherm. The electrochemical results implied that the as-prepared FCDs inhibitor could effectively suppress the corrosion of Q235 steel in 1 M HCl solution. At the same time, the inhibition efficiency of steel in 1 M HCl solution was more than 90% when the inhibitor concentration exceeded 100 mg/L. This excellent property was attributed to the coverage of adsorption film on the steel surface, which conformed to the Langmuir adsorption model. In addition, the analysis of adsorption isotherm displayed that the adsorption mechanism was the physicochemical interaction at the steel/solution interface.